Low-molecular-mass antioxidants in parasites - Krauth-Siegel, Renate; Leroux, Alejandro E. (Antioxidants & redox signaling, 2012)
Significance: Parasitic infections continue to be a major problem for global human health. Vaccines are practically not available and chemotherapy is highly unsatisfactory. One approach toward a novel antiparasitic drug development is to unravel pathways that may be suited as future targets. Parasitic organisms show a remarkable diversity with respect to the nature and functions of their main low-molecular-mass antioxidants and many of them developed pathways that do not have a counterpart in their mammalian hosts. Recent Advances: Work of the last years disclosed the individual antioxidants employed by parasites and their distinct pathways. Entamoeba, Trichomonas, and Giardia directly use cysteine as main low-molecular-mass thiol but have divergent cysteine metabolisms. Malarial parasites rely exclusively on cysteine uptake and generate glutathione (GSH) as main free thiol as do metazoan parasites. Trypanosomes and Leishmania have a unique trypanothione-based thiol metabolism but employ individual mechanisms for their cysteine supply. In addition, some trypanosomatids synthesize ovothiol A and/or ascorbate. Various essential parasite enzymes such as trypanothione synthetase and trypanothione reductase in Trypanosomatids and the Schistosoma thioredoxin GSH reductase are currently intensively explored as drug target molecules. Critical Issues: Essentiality is a prerequisite but not a sufficient property of an enzyme to become a suited drug target. The availability of an appropriate in vivo screening system and many other factors are equally important. Future Directions: The current organism-wide RNA-interference and proteome analyses are supposed to reveal many more interesting candidates for future drug development approaches directed against the parasite antioxidant defense systems. Antioxid. Redox Signal. 17, 583-607.
Online ahead of editing: November 5, 2011
Gesehen am 19.11.2018